The use of silver in the preparation and purification of water - Kyryk, Tetiana; Babii, Vitalii; Honcharenko, Iryna; Mykhailenko, Oleksii (Problems of Environmental Biotechnology, 2021)
Research and analysis of synthesis methods and identification of nanosized forms of Argentum such as colloidal state and uncharged nanoparticle, as well as comparison of their properties and bactericidal action depending on the nature of the particle, were carried out.